2009
DOI: 10.1080/02699050902774170
|View full text |Cite
|
Sign up to set email alerts
|

High-level mobility outcomes following acquired brain injury: A preliminary evaluation

Abstract: Significant recovery in high-level mobility was achieved during a 3 month running programme. People with chronic ABI may also expect to benefit from retraining high-level mobility. Clinical trials are needed to assess the effectiveness of training programmes for high-level mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…The two case studies illustrated how the conceptual framework could be applied for people with contrasting movement disorders; in this instance one person with hemi-spasticity and one person with ataxia. Williams and Morris [24] also used this conceptual framework to investigate the feasibility of retraining high-level mobility in a cohort of 28 people with a variety of neurological conditions including TBI and stroke. It was demonstrated that clinically significant improvements in high-level mobility can be achieved, even for patients with conditions of longstanding duration.…”
Section: Introductionmentioning
confidence: 99%
“…The two case studies illustrated how the conceptual framework could be applied for people with contrasting movement disorders; in this instance one person with hemi-spasticity and one person with ataxia. Williams and Morris [24] also used this conceptual framework to investigate the feasibility of retraining high-level mobility in a cohort of 28 people with a variety of neurological conditions including TBI and stroke. It was demonstrated that clinically significant improvements in high-level mobility can be achieved, even for patients with conditions of longstanding duration.…”
Section: Introductionmentioning
confidence: 99%
“…11,14 Individuals, months to years after TBI, were able to improve their running abilities after a 3-month running program. 54 Brown and colleagues 55 found that patients with central vestibular dysfunction improved in both subjective and objective measures of balance after physical therapy intervention. Outcome is better for patients with TBI when there is an isolated peripheral vestibular impairment.…”
Section: Discussionmentioning
confidence: 98%
“…Miller et al 13 also investigated the use of partial body weight support on a treadmill to improve running ability for a 38-year-old man who had a suffered a stroke. Most recently, Williams and Morris 11 investigated the feasibility of retraining high-level mobility in a cohort of people with a variety of neurological conditions including TBI and stroke. Although it was demonstrated that clinically meaningful improvements in high-level mobility could be made even for patients with conditions of longstanding duration, no details were provided as to the nature of the mobility deficits or the intervention provided.…”
mentioning
confidence: 99%